A cadeia produtiva do camarão cultivado no estado do Ceará: uma análise crítica - Figueiredo Júnior, Carlos Alberto (2006)
It was tried to identify and analyze the productive chain of the farm shrimp in the state of Ceará. It was used a system approach, appropriated for studies that aim to analyze the dynamic of a productive chain. The data used in this research had secondary and primary origin, through application of questionnaires with representative agents of each segment. Among the results reached, it is worth to mention: The activity goes through a crisis period thar affected all the segments of the chain; the ration manufacturers, after successive price reduction, search for ways to obtain ration with low costs; the laboratories of larva culture face the genetic exhaustion of the matrices with clear effects in the resistance of the shrimp to diseases; the farmers consider that the main troubles faced are, by order of importance: the restrictions of the environment body, the diseases and the fall of the rate of exchange; the export companies resent of the high level of demands of the importers; the shrimp is still considered a noble product, scarcely accessible to low income consumers. There are divergent opinions (NGO's, specialist and public institutions) about the environment impacts caused by the shrimp farming. Among the conclusions of the study, it is qouted; the sector faces a crisis, caused by many factors; there is big competition among agents of some segments of the chain; there is no integration among the agents of the same segment and among different segments of the chain, what intensifies the problem faced recently by the activity.